Mother’s Day Superstorms: Pre- and Post-storm Evolutionary Patterns of ARs 13664/8 - Mausumi Dikpati; Marianna B. Korsós; Aimee A. Norton; Breno Raphaldini; Kiran Jain; Scott W. McIntosh; Peter A. Gilman; Andre S. W. Teruya; Nour E. Raouafi (The Astrophysical Journal, 2025)
In the week including Mother’s Day 2024, active region (AR) 13664 became superactive when AR 13668 emerged nearby, causing multiple X-class flares and coronal mass ejections, and an increase in activity level similar to that inferred from geomagnetic storms associated with the historic 1859 events. By analyzing both global warped toroids on which the active regions are strung, and active-region-scale magnetic flux and helicity, we find (i) the north and south toroids have nearly identical warped patterns, with mostly longitudinal wave numbers m  = 1–3; (ii) in three longitude intervals the north and south toroids were tipped away from each other in latitude, with a longitude phase shift between them, creating locations most prone to AR eruptions; (iii) on an active region scale, vector magnetic fields deviate far from potential fields, and therefore contain large amounts of magnetic “free energy” available for conversion into kinetic energy and high-temperature radiation; (iv) the positive and negative polarities converge toward each other, facilitating reconnection and magnetic energy release; and (v) rapid changes in magnetic helicity, caused by helicity injection from below that creates helicity imbalances. Despite the coarser resolution of GONG magnetograms, the derived global toroids are strikingly similar to those derived from the Solar Dynamics Observatory's Helioseismic and Magnetic Imager. We conclude that the Mother’s Day superstorms were caused by enhanced magnetic complexity occurring due to intricate interactions among multiple active regions emerging at nearly the same locations. This suggests that predicting the locations of magnetically complex active regions, and studying and tracking their eruptive states using different proxy parameters can greatly improve our ability to forecast intense storms, not only hours but potentially weeks in advance.